The Effect of spacing and fertilizer levels on growth and yield of garden pea (Pisum sativum) in the humid temperate zone of north-western Himalayas - THAKUR, SHIPRA; KATOCH, VIVEKA; RANA, SURINDER SINGH (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during winter (rabi) season 2019–20 and 2020–21 at Chaudhary Sarwan Kumar Himachal Pradesh Agricultural University, Palampur, Himachal Pradesh to study effect of different spacings and fertility levels on growth and productivity of newly developed powdery mildew resistant pyramid line of garden pea (Pisum sativum L.), Line 1–2. The experiment was laid out in randomised block design (RBD) with Azad Pea-1 as a standard check, replicated thrice. Treatment combinations comprising of three spacings (30 cm × 10 cm, 45 cm × 10 cm and 60 cm ×10 cm) and four fertility levels [100% RDF (recommended dose of fertilizer), 75% RDF, 125% RDF and 50 % N through urea + 50% N through FYM+100% Phosphorous (P) and Potassium (K)] were assigned to each plot along with Azad pea-1 as standard check. The results revealed that narrow spacing of 30 cm ×10 cm resulted in minimum number of days to 50% flowering and minimum number of days to first picking. Maximum shelling percentage was also observed in 30 cm × 10 cm spacing with application of 125% RDF. Spacing of 45 cm × 10 cm resulted in maximum number of primary branches/plant, number of nodes/plant, pod yield/ha, pod length and number of seeds/pod at 100% recommended dose of fertilizer. Wide spacing of 60 cm × 10 cm accompanied with 125% fertility level resulted in maximum number of pods/plant and pod yield/plant. Maximum seed yield/plant was recorded at 50% N through urea + 50% N through FYM + 100% PK. Interaction effects of 100% fertility level and 50% N through urea + 50% N through FYM + 100% PK with spacing of 45 cm × 10 cm resulted in better performance of Line 1–2 for gross return, net return and benefit cost ratio.